Impact of childhood adversities on specific symptom dimensions in first-episode psychosis. Issue 2 (18th September 2015) - Ajnakina, O.; Trotta, A.; Oakley-Hannibal, E.; Di Forti, M.; Stilo, S. A.; Kolliakou, A.; Gardner-Sood, P.; Gaughran, F.; David, A. S.; Dazzan, P.; Pariante, C.; Mondelli, V.; et al.
Abstract : Background: The relationship between childhood adversity (CA) and psychotic disorder is well documented. As the adequacy of the current categorical diagnosis of psychosis is being increasingly questioned, we explored independent associations between different types of CA and specific psychotic symptom dimensions in a well-characterized sample of first-episode psychosis (FEP) patients. Method: This study involved 236 FEP cases aged 18–65 years who presented for the first time to psychiatric services in South London, UK. Psychopathology was assessed with the Positive and Negative Syndrome Scale and confirmatory factor analysis was used to evaluate the statistical fit of the Wallwork/Fortgang five-factor model of psychosis. CA prior to 17 years of age (physical abuse, sexual abuse, parental separation, parental death, and being taken into care) was retrospectively assessed using the Childhood Experience of Care and Abuse Questionnaire. Results: Childhood sexual abuse [ β = 0.96, 95% confidence interval (CI) 0.40–1.52], childhood physical abuse ( β = 0.48, 95% CI 0.03–0.93) and parental separation ( β = 0.60, 95% CI 0.10–1.11) showed significant associations with the positive dimension; while being taken into care was associated with the excited dimension ( β = 0.36, 95% CI 0.08–0.65), independent of the other types of CA. No significant associations were found between parental death and any of the symptom dimensions. Conclusions: A degree of specificity was found in the relationships between different types of CA and psychosis symptom dimensions in adulthood, suggesting that distinct pathways may be involved in the CA–psychosis association. These potentially different routes to developing psychosis merit further empirical and theoretical exploration.